PENGARUH KOMPETENSI SUMBER DAYA MANUSIA TERHADAP PENGELOLAAN ALOKASI DANA DESA (ADD) (Studi Kasus Di Desa Neglasari, Desa Cijangkar, Desa Bojongkalong, Desa Mekarsari, Desa Bojongsari Dan Desa Kertaangsana Kecamatan Nyalindung KabSukabumi Jawa Barat - Raharja, Anisa Dewi; Suherman, Acep; Alamsyah , Sakti (Universitas Nusantara PGRI Kediri, 2020)
This research aims to determine the influence of human resources competency, on the management of village fund allocation. The survey was devoted only to 6 villages in the Nyalindung sub-district of Sukabumi Regency. The study used quantitative methods with data collection techniques used by literature studies, dissemination of questionnaires, and documentation. The number of questionnaire distributed by researchers amounted to 70 questionnaires addressed to village heads, village secretaries, village Treasurer, chief affairs, sexy heads, and village consultative bodies. To know the regression model is carried out testing of normality, multi-kolienirity, and heteroskedastisity. IBM SPSS 26 for Windows software. The results of the study showed that the competency of human resources simultaneously has a significant influence on the management of Village Fund allocation (ADD). The result of coefficient of determination test indicates that the value of R Square in this study is 0.731 or at 73.1%. This can mean that the human resource competency variables influence the management variables of the village's funding allocation by 73.1%, while the remaining 26.9% is influenced by other factors not examined in this study.